The Impact of Developing the EFL University Students’ Awareness in the Use of Pragmatic Markers on their Essay Writing ability - Katti, Walaa Jabbar (Al-Adab Journal, 2020)
Writing is not only employs the procedure of a good written text, but depicts and values the coherence as well as the cohesion, too. Composing a lot of sentences without considering the cohesive ties fails to negotiate the inter-related events intended to be decoded by the reader. Then the presence of text markers is a necessary condition to have a smooth and enjoyable written text. Thus, writing a good essay needs the mastery of choosing the suitable pragmatic markers. Pragmatic markers, according to many writers, are a crucial part of learners’ strategic competence. However, Pragmatic markers comprise a functional class of linguistic items that do not typically change the propositional meaning of an utterance but are essential for the organization and structuring of discourse, for marking the writer’s attitudes to the proposition being expressed as well as for facilitating processes of pragmatic inferences. Pragmatic markers have been seen as set of syntactically diverse linguistic items (for example, of course, surely, quite frankly, incidentally, thus, well and so on). Thus, the essence of this study is to examine the students’ performance in the use of the pragmatic markers. It also aims to investigate the effects of developing the pragmatic markers on their essay writing abilities. In addition, the present study intends to answer the following questions: How is the performance of the students in essay writing? What is the difference between the experimental group who will achieve the treatment sessions during the present experiment and the control group who will held back to receive such a treatment? What are the significant relationship between developing students’ awareness in the use of pragmatic markers and their essay writing ability?